Double Strand Break Unwinding and Resection by the Mycobacterial Helicase-Nuclease AdnAB in the Presence of Single Strand DNA-binding Protein (SSB) - Unciuleac, Mihaela-Carmen (American Society for Biochemistry and Molecular Biology, 2010)
Mycobacterial AdnAB is a heterodimeric DNA helicase-nuclease and 3′ to 5′ DNA translocase implicated in the repair of double strand breaks (DSBs). The AdnA and AdnB subunits are each composed of an N-terminal motor domain and a C-terminal nuclease domain. Inclusion of mycobacterial single strand DNA-binding protein (SSB) in reactions containing linear plasmid dsDNA allowed us to study the AdnAB helicase under conditions in which the unwound single strands are coated by SSB and thereby prevented from reannealing or promoting ongoing ATP hydrolysis. We found that the AdnAB motor catalyzed processive unwinding of 2.7–11.2-kbp linear duplex DNAs at a rate of ∼250 bp s(−1), while hydrolyzing ∼5 ATPs per bp unwound. Crippling the AdnA phosphohydrolase active site did not affect the rate of unwinding but lowered energy consumption slightly, to ∼4.2 ATPs bp(−1). Mutation of the AdnB phosphohydrolase abolished duplex unwinding, consistent with a model in which the “leading” AdnB motor propagates a Y-fork by translocation along the 3′ DNA strand, ahead of the “lagging” AdnA motor domain. By tracking the resection of the 5′ and 3′ strands at the DSB ends, we illuminated a division of labor among the AdnA and AdnB nuclease modules during dsDNA unwinding, whereby the AdnA nuclease processes the unwound 5′ strand to liberate a short oligonucleotide product, and the AdnB nuclease incises the 3′ strand on which the motor translocates. These results extend our understanding of presynaptic DSB processing by AdnAB and engender instructive comparisons with the RecBCD and AddAB clades of bacterial helicase-nuclease machines.